2015
DOI: 10.6000/1929-4247.2015.04.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Potentials, Experiences and Outcomes of a Comprehensive Community Based Programme to Address Malnutrition in Tribal India

Abstract: This paper demonstrates the effect of an innovative community-based management programme on acute malnutrition among children under three years of age, through an observational longitudinal cohort study in tribal blocks in central-eastern India. The key components of the programme include child care through crèches, community mobilisation and systems strengthening to ensure better child feeding and caring practices and delivery of public health and nutrition services. For a cohort of 587 children, the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Other facility and community‐based nutrition programmes in India have had similarly low performance in recovery rates (Aguayo et al, ; V. M. Aguayo et al, ; Burza et al, ; Prasad & Sinha, ; Singh et al, ). In the only Indian multicentre randomized trial evaluating the efficacy of ready‐to‐use therapeutic food (RUTF) for community‐based treatment of uncomplicated severe acute malnutrition, recovery rates were below 41% at 8 weeks of treatment; after extending to 16 weeks, over 40% of children had not yet recovered (Bhandari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other facility and community‐based nutrition programmes in India have had similarly low performance in recovery rates (Aguayo et al, ; V. M. Aguayo et al, ; Burza et al, ; Prasad & Sinha, ; Singh et al, ). In the only Indian multicentre randomized trial evaluating the efficacy of ready‐to‐use therapeutic food (RUTF) for community‐based treatment of uncomplicated severe acute malnutrition, recovery rates were below 41% at 8 weeks of treatment; after extending to 16 weeks, over 40% of children had not yet recovered (Bhandari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In April 2013, it was decided that for the purpose of uniformity across crèches, heights would be measured at entry point and in the months of May and November each year for all children, irrespective of their date of admission. The outcomes of 45 SAM children were reported early in the program as part of a cohort of 587 children in all categories [1]. These 45 children are also included in the current analysis.…”
Section: Aam Is Being Collaboratively Implemented By Publicmentioning
confidence: 99%
“…ommunity-based management of malnutrition remains a challenge for India with limited numbers of Nutritional Rehabilitation Centers (NRC) providing facility-based care for a small proportion of children with Severe Acute Malnutrition (SAM) [1,2]. Action Against Malnutrition (AAM) is a model that offers comprehensive care to children below the age of 3 years through day-care facilities, and works closely with women on nutrition-action through Participatory learning and action (PLA) cycles, home visits, and close liaison with related government facilities and services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have suggested that, nutrition counselling, particularly focusing on improving infant and young child feeding practices, may be as effective as specialized foodbased interventions for the treatment of MAM (Roy et al, 2005;Prasad and Sinha, 2015).…”
Section: Management Of Mammentioning
confidence: 99%